Explanation of cryptic hint: By Fermat's Two square theorem, since \( 65 = 5 \times 13 = ( 2^2 + 1^2 ) ( 2^2 + 3^2 ) \), we can write 65 as the sum of two (positive) squares in two distinct ways.

You have 3 variables and 2 equations, so you do not have a completely determined system.

Though, the claim is that \( a^2 - b^2 + c^2 \) is independent of the actual values. The point of the question is to prove that the expression is always equal to 1.

I don't know whether this method is valid , but we learn from mistakes and hence, I try:

Computing for \(b\) from both the equations,

\[b=\dfrac{a+8c-4}{7}=\dfrac{7+c-8a}{4}\]

Now simplifying the two equations at the right , we get \(12a+5c=13\Rightarrow 12(13a)+5(13c)=13^2\) which imitates the Pythagorean triplet \(12^2+5^2=13^2\) and then comparing them we have \(13a=12 \ , \ 13c=5\) which when substituted in the either of the first equations , we have \(b=0\). Now substituting the acquired values in required expression we have \(a^2-b^2+c^2=1\).

This solution is incomplete since it assumes that \(13a,13c\) are integers.

This method doesn't constitute a proof, since you're essentially substituting \( b =0 , a = \frac{12}{13}, c = \frac{5}{13} \).

If you want a proof by substitution, you could
1. Determine \(a\) and \(b\) in terms of \(c\) only.
2. Substitute these values into \( a^2 - b^2 + c^ 2\).
3. Hope that everything cancels out (which it should, if your arithmetic is correct).

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestDenote the two equations \((1)\) and \((2)\) respectively:

\((1)-2(2)\) gives us \(a+b=\frac {2}{3}(1+c)\)

\(2(1)+(2)\) gives us \(a-b=\frac {3}{2}(1-c)\)

So \(a^2-b^2+c^2=(a+b)(a-b)+c^2=1-c^2+c^2=1\).

Log in to reply

Nice question

Cryptic Hint:\( 65 = 5 \times 13 \). These are both primes of the form \( 1 \pmod{4} \).Log in to reply

Don't you mean "of the form \( 1 \pmod{4} \)"?

Log in to reply

Oooops, yes I do. Edited. Thanks!

Log in to reply

Sir, can you explain how you got this? I'm sorry I do not know this method. :)

Log in to reply

Direct Hint:\( 65 = 1^2 + 8^2 = 7^2 + 4^2 \)Explanation of cryptic hint: By Fermat's Two square theorem, since \( 65 = 5 \times 13 = ( 2^2 + 1^2 ) ( 2^2 + 3^2 ) \), we can write 65 as the sum of two (positive) squares in two distinct ways.

Log in to reply

Log in to reply

We can use matrices to find the values of a,b,c

Log in to reply

You have 3 variables and 2 equations, so you do not have a completely determined system.

Though, the claim is that \( a^2 - b^2 + c^2 \) is independent of the actual values. The point of the question is to prove that the expression is always equal to 1.

Log in to reply

I don't know whether this method is valid , but we learn from mistakes and hence, I try:

Computing for \(b\) from both the equations,

\[b=\dfrac{a+8c-4}{7}=\dfrac{7+c-8a}{4}\]

Now simplifying the two equations at the right , we get \(12a+5c=13\Rightarrow 12(13a)+5(13c)=13^2\) which imitates the Pythagorean triplet \(12^2+5^2=13^2\) and then comparing them we have \(13a=12 \ , \ 13c=5\) which when substituted in the either of the first equations , we have \(b=0\). Now substituting the acquired values in required expression we have \(a^2-b^2+c^2=1\).

This solution is incomplete since it assumes that \(13a,13c\) are integers.

Log in to reply

This method doesn't constitute a proof, since you're essentially substituting \( b =0 , a = \frac{12}{13}, c = \frac{5}{13} \).

If you want a proof by substitution, you could

1. Determine \(a\) and \(b\) in terms of \(c\) only.

2. Substitute these values into \( a^2 - b^2 + c^ 2\).

3. Hope that everything cancels out (which it should, if your arithmetic is correct).

Log in to reply

Slightly easier approach that follows from my hint. Consider:

\[ (a-7b+8c)^2 + (8a+4b-c)^2 \]

Notice that the cross terms cancel out.

This exploits the symmetry of the values, and the observation that \( 1^2 + 8^2 = 4^2 + 7^2\).

Log in to reply

2^{0}

Log in to reply

0

Log in to reply

Eliminating \(a,b,c\) one by one from both equations we get 3 equations:

\(13a+5b=12\) ...1

\(13c-12b=5\) ...2

\(12a-5c=13\) ...3

Again by elimination of each of \(a,b\) and \(c\),we get \(a=\frac{13}{12},b=-\frac{5}{12},c=0\)

Putting them in \(a^{2}-b^{2}+c^{2}\) we get \(\boxed{1}\).

Log in to reply

It is wrong to simply assume that \(c=0\). We must show that the answer is independent of \(c\).

Log in to reply